2018
DOI: 10.1371/journal.pone.0202327
|View full text |Cite
|
Sign up to set email alerts
|

Moral growth mindset is associated with change in voluntary service engagement

Abstract: Incremental implicit theories are associated with a belief regarding it is possible to improve one’s intelligence or ability through efforts. Previous studies have demonstrated that incremental implicit theories contributed to better academic achievement and positive youth development. Our study aimed to examine whether incremental implicit theories of morality significantly influenced change in students’ engagement in voluntary service activities. In our study, 54 Korean college students for Study 1 and 180 K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…The pretest engagement was surveyed before the beginning of the intervention period, and the posttest survey was conducted 12 weeks from the pretest survey. In addition, to control for any possible effects due to individual differences in participants' mindset regarding moral development, the study measured their moral growth mindset based on their volunteer service engagement [24]. Finally, the study surveyed how participants responded to intervention materials and activities, by collecting data on moral elevation, perceived moral excellence, and perceived difficulty to emulate presented moral behaviors after the end of the intervention period.…”
Section: Learning Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…The pretest engagement was surveyed before the beginning of the intervention period, and the posttest survey was conducted 12 weeks from the pretest survey. In addition, to control for any possible effects due to individual differences in participants' mindset regarding moral development, the study measured their moral growth mindset based on their volunteer service engagement [24]. Finally, the study surveyed how participants responded to intervention materials and activities, by collecting data on moral elevation, perceived moral excellence, and perceived difficulty to emulate presented moral behaviors after the end of the intervention period.…”
Section: Learning Datasetmentioning
confidence: 99%
“…Before the intervention period, to examine whether a participant possessed either a growth or fixed mindset in the domain of morality, Han et al [23] assessed their moral growth mindset with a questionnaire. Han et al [24] reported that the presence of moral growth mindset, which is associated with a belief that one can be a morally better person through intentional efforts (e.g., participating in prosocial activities), was significantly associated with an increase in volunteering. Thus, we decided to control for this factor in our current analyses.…”
Section: Moral Growth Mindsetmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth mindset concerns the belief that an individual's basic attributes are malleable and can be cultivated through endeavors (Dweck et al, 1995;Dweck, 2015). Recently, a burgeoning body of research has demonstrated that high levels of growth mindset are positively related to optimal functions across the psychological, social, and academic domains, such as psychological well-being (Zeng et al, 2016), less mental health difficulties (Schleider et al, 2015;Schleider and Weisz, 2018;Wang et al, 2019), prosocial tendency (Han et al, 2018), self-regulation (Burnette et al, 2013;Lan et al, 2019a), learning motivation (Burnette et al, 2018), and academic achievement (Yeager et al, 2016;Wang et al, 2020). Given the salience role of growth mindset in life courses, the knowledge about the contextual and individual antecedents of growth mindset is still limited in existing research.…”
Section: Introductionmentioning
confidence: 99%